Government Primary School Services In Indonesia-Malaysia’s Border Area of Entikong - Retnowati Retnowati; Rahmat Salam; Maria Sri Iswari; Mawar Mawar (Iapa Proceedings Conference, 2018)
Primary School is part of the 9-year compulsory education policy for children aged 6-7 years, during their 6 years of learning. The longest study time between the levels of education in Indonesia. The earlier statement means that Primary School Education is very important for the basic’s children development in Emotional Quation , Intelligence Quation, Adversity Quation, Spiritual Quation and Creativity Quation consecutively . Moreover, Entikong District - Sanggau Regency, West Kalimantan Province is one of the Priority Locations in the border region. The said service to public elementary school children must be in a good quality. Meanwhile the Services in SD Negeri 05 Suruh Tembawang Entikong are still far from expectations. This study aims to analyze the services to Suruh Tembawang Public Elementary School 05 Entikong District by the Sanggau Regional Government. The analysis used taken from Parasuraman opinions with the following indicators: Tangibles, Reliability, Responsiveness, Assurance and Emphaty. The Research Approach uses a Qualitative Approach and the Research Method is Descriptive. Data Collection Techniques: Interviews, Focus Group Discussion and Documentation. Informant Selection Techniques: Purposive. Data Analysis with Miles and Huberman. Data Validity Test with Triangulation. Discussion: Primary Schools in Priority Locations do not receive much attention, are very detrimental to society. In fact, they can reach other countries quickly as seen from their eyes. In terms of Indonesia's sense of nationality, it is quite vulnerable, while in education context, will get worse, if the conditions are not promptly corrected. Research results: Tangibles: It is difficult to access connecting bridge facilities with sub-districts, classrooms are damaged, there is no official residence, lack of teaching aids, computers are not available; Reliability: teaching is less reliable for teacher, responsiveness: unresponsive, Assurance: remains trusted by the community; Emphaty: teachers in high students as well as people empathize with teachers. Conclusion: There are lack of quality services for facilities and infrastructure in SD Negeri 05 Suruh Tembawang and not in accordance with what are needed. Recommendation: Local government should increase cooperation between SKPD (Dinas PU and Dinas Pendidikan Kebudayaan); Exploring the company's CSR; Inviting Universities for Community Service Program Internships.